The Efficacy of Agricultural Cooperatives Towards Enhancing Food Security in Rural Areas: Mbombela Local Municipality, Mpumalanga Province - Ndlovu, Confidence; Masuku, Mfundo M. (Technium Social Sciences Journal, 2021)
This paper aimed to explore the effectiveness of agricultural cooperatives towards the enhancement of food security in rural areas. The formation of agricultural cooperatives in South Africa is a prerequisite for obtaining government support concerning activities aimed at social and economic development. It is well-documented that agricultural cooperatives are business entities and vehicles for food security. However, this review sustained that agricultural cooperative do not completely alleviate the vulnerability of food-insecure households because of the dearth of institutional support and sufficient productive resources. Focus group discussions with six agricultural cooperatives and four face-to-face in-depth interviews with municipal officials were conducted to envisage the improvement of food security through agricultural cooperatives. Using thematic analysis to analyse data, findings confirmed that institutional support improves the efficiency of agricultural cooperatives at the local level. Furthermore, institutional support enhances productivity which renders the cooperatives as a supplementary intervention to food security. However, there is a gap in enabling access to agricultural inputs, such as funding for access to farming equipment. This paper recommends the implementation of a cooperative management structure to enhance planning, coordination, and monitoring. The municipality should review the agricultural cooperative governance frameworks to achieve enabling environments for farming activities